(untitled) (International Journal of Environmental Sciences, 2025)
Introduction: Duodenal atresia is a leading cause of neonatal intestinal obstruction and is commonly associated with trisomy 21 (Down syndrome). We report a case of duodenal atresia with trisomy 21, a condition rarely documented in Indonesian literature, emphasizing the role of early detection in optimizing outcomes. Case Presentation: A 36-year-old woman (G2​P1​A0​) was referred to our tertiary center with polyhydramnios. Prenatal ultrasound revealed the characteristic "double bubble" sign, nasal bone hypoplasia, and hypotelorism. Postnatal genetic testing confirmed trisomy 21. Surgical exploration confirmed an annular pancreas causing the duodenal obstruction, which was successfully corrected with a duodenojejunostomy. The infant had an excellent postoperative recovery.Discussion: Duodenal atresia typically results from failed intestinal recanalization. This case highlights the pivotal role of prenatal ultrasound in identifying not only structural anomalies but also soft markers that guide further genetic investigation. Early diagnosis is particularly critical in lower-middle-income settings, as it facilitates timely referral and multidisciplinary planning, which are key to improving perinatal management. Conclusion: Early prenatal diagnosis of duodenal atresia is a critical trigger for a cascade of interventions including genetic counseling, coordinated delivery planning, and prompt surgical management. This report contributes to the limited published data from Southeast Asia, underscoring the importance of building regional evidence to enhance perinatal care.